2001
DOI: 10.1093/eurpub/11.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use by early adolescents in Norway

Abstract: Several hypotheses that might account for the recent increase were examined with the most likely factor being Norway's low allocation of resources for educational interventions and public information campaigns during the years studied. However, in the past 2 years Norway has undertaken a number of new tobacco control initiatives that may result in reversal of the most recent trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…Addiction to smoking typically begins during childhood [17]. Recent studies raised questions about the model on the natural course of onset of cigarette use [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addiction to smoking typically begins during childhood [17]. Recent studies raised questions about the model on the natural course of onset of cigarette use [49].…”
Section: Discussionmentioning
confidence: 99%
“…Sex or/and gender differences in relation to adolescent [16][17][18][19][20] and adults [21][22][23] tobacco smoking behaviour have been described mostly in industrialised countries. Recent statistics published in 2005 by the "Observatoire Français des drogues et desagency dedicated to the fight against addictions), indicated that the proportion of daily tobacco smokers was decreasing with age for both sexes but was the highest in young adults (25-34 years 40% for men and 30% for women) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Usage of oral smokeless tobacco is gaining popularity throughout the western world especially with adolescents. [33][34] Tobacco in the form of Swedish moist oral snuff (snus) is today highly prevalent in the Swedish male population, and has been increasing during the past decades from 22% to 30%. 35 The proposal that usage of smokeless tobacco might lead to smoking behavior [36][37] has been of major concern, however some results suggest snuff dipping to be more closely related to cessation of smoking (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1997 and 2005, the proportion of daily users of snuff increased by two percentage units, among both genders. In contrast, studies of the smoking habits of Norwegian (Braverman, Svendsen, Lund, & Aarø, 2001) and German (Maziak, Rzehak, Keil, & Weiland, 2003) adolescents show opposite trends. These studies conclude that the increased figures may be due to the fact that over the past few years, fewer resources have been spent on tobacco prevention among adolescents.…”
Section: Discussionmentioning
confidence: 83%